Cell culture-derived influenza vaccines in the severe 2017–2018 epidemic season: a step towards improved influenza vaccine effectiveness. (December 2018) - Barr, Ian; Donis, Ruben; Katz, Jacqueline; McCauley, John; Odagiri, Takato; Trusheim, Heidi; Tsai, Theodore; Wentworth, David
Abstract The 2017–2018 seasonal influenza epidemics were severe in the US and Australia where the A(H3N2) subtype viruses predominated. Although circulating A(H3N2) viruses did not differ antigenically from that recommended by the WHO for vaccine production, overall interim vaccine effectiveness estimates were below historic averages (33%) for A(H3N2) viruses. The majority (US) or all (Australian) vaccine doses contained multiple amino-acid changes in the hemagglutinin protein, resulting from the necessary adaptation of the virus to embryonated hen's eggs used for most vaccine manufacturing. Previous reports have suggested a potential negative impact of egg-driven substitutions on vaccine performance. With BARDA support, two vaccines licensed in the US are produced in cell culture: recombinant influenza vaccine (RIV, Flublok™) manufactured in insect cells and inactivated mammalian cell-grown vaccine (ccIIV, Flucelvax™). Quadrivalent ccIIV (ccIIV4) vaccine for the 2017–2018 influenza season was produced using an A(H3N2) seed virus propagated exclusively in cell culture and therefore lacking egg adaptative changes. Sufficient ccIIV doses were distributed (but not RIV doses) to enable preliminary estimates of its higher effectiveness relative to the traditional egg-based vaccines, with study details pending. The increased availability of comparative product-specific vaccine effectiveness estimates for cell-based and egg-based vaccines may provide critical clues to inform vaccine product improvements moving forward.